Performance and Energy Analysis of a Fuel Cell Electric Vehicle - Sahin, Habip; Esen, Hikmet (Ieee-Inst Electrical Electronics Engineers Inc, 2025)
In the last century, individual transportation vehicles become much more common and they cause great environmental problems. Renewable and sustainable energy solutions will help reduce these environmental problems. Thus, there is a trend towards electric vehicle from internal combustion engine vehicle. Fuel cell electric vehicles, with their competitive driving range, short refueling time and zero emissions, are considered the most likely solution among the vehicle technologies of the future. Since the fuel cell is late to meet the sudden power requirements, it must be hybridized with a second energy device having high power dynamics. In this study, a mid-size passenger vehicle, having 80 kW fuel cell stack supported by a 1.97 kWh battery pack, is modeled with Matlab. The vehicle is simulated on Worldwide Harmonized Light Vehicle Test Procedure (WLTP) Class 3 driving cycle and fuel consumption and range values are 2.15 L/100 km as gasoline equivalent and 859.2 km, respectively. The average efficiency of the internal permanent magnet synchronous motor providing vehicle propulsion is 93.4% throughout the cycle. The overall efficiency of the vehicle is found to be 56.2%, based on the higher heating value of the consumed hydrogen. The emission value of the vehicle is 75.1 gCO(2)e/km according to the average hydrogen production emission intensity.
Keywords: Hydrogen; Batteries; State of charge; Brakes; Wheels; Transportation; Fuel economy; Electricity; Electric vehicle; energy efficiency; fuel cell; hydrogen; vehicle performance; hydrogen; vehicle performance